Therapeutic potential of PLK1 inhibition in triple-negative breast cancer - Ueda, Ai; Oikawa, Keiki; Fujita, Koji; Ishikawa, Akio; Sato, Eiichi; Ishikawa, Takashi; Kuroda, Masahiko; Kanekura, Kohsuke (Laboratory investigation, 2019)
Triple negative breast cancer (TNBC) is responsible for significant number of breast cancer-associated deaths because of lacking of successful molecular-targeted therapy. To explore a therapeutic target for TNBC, we performed a siRNA-mediated knockdown screening and identified Polo-like kinase 1 (PLK1) as a potential therapeutic target for TNBC. Knockdown of PLK1 as well as a small compound inhibitor for PLK1, BI-2536, induced G2/M arrest and created polyploid cell population, shown by increased DNA content and nuclear size. Inhibition of PLK1 eventually triggered apoptosis in multiple TNBC cell lines. In addition, we confirmed that PLK1 was significantly overexpressed in the tissues from TNBC patients compared with the tissues of normal mammary glands and benign breast tumors. Our data indicated that PLK1 plays a pivotal role in the regulation of mitosis of TNBC cells. Although future in vivo studies are warranted, targeting PLK1 by a selective inhibitor such as BI-2536 can be an attractive molecular-targeted therapy for TNBC.